Mid-term outcomes of percutaneous pulmonary valve replacement with Edwards-Sapien bioprosthesis in native right ventricular outflow tract - Yassin Belahnech; Gerard Martí-Aguasca; Laura Dos-Subirà; Pedro Betrian-Blasco; Bruno García del Blanco; Maria Calvo-Barceló; Eduard Ródenas-Alesina; Antonia Pijuan-Domènech; Ferran Gran; Queralt Ferrer; Gemma Giralt-García; Berta Miranda; et al. (Scientific Reports)
Abstract Information on mid-term outcomes of percutaneous pulmonary valve replacement (PPVR) with the Edwards Sapien (ES) valve in the native right ventricular outflow tract (RVOT) are limited. This study assesses mid-term outcomes in 76 patients who underwent PPVR between 2016 and 2022, comparing native (40.8%) and non-native (59.2%) RVOTs. The primary endpoint was a composite of endocarditis, reinterventions, and cardiovascular death and secondary outcomes included prosthetic valve dysfunction (PVD), tricuspid regurgitation (TR), right ventricular ejection fraction (RVEF), and indexed ventricular volumes. The median patient age was 23.9 years. Pulmonary regurgitation was predominant in the native RVOT group (67.7%), while pulmonary stenosis or combined lesions were more common in the non-native group (90.9%). Procedural success was 98.7%. After a median follow-up of 3.3 years, there was no significant difference in freedom from the primary outcome between groups (87.1% native vs. 93.1% non-native, p = 0.875). Endocarditis and reinterventions occurred at 1.2 per 100 patient-years, and PVD at 3.19 per 100 patient-years, with no differences between groups. A 1-year reduction in ventricular volumes and TR was seen only in the non-native group, with no improvement in RVEF. Overall, PPVR with the ES valve demonstrates satisfactory mid-term outcomes in both native and non-native RVOTs.